An Overview of Municipal Solid Waste Collection in Singapore, Mongolia, and Nepal - Laraib Ehtasham (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
Municipal solid waste (MSW), including refuse and non-hazardous waste, is generated mainly from households. This article adopts the approach of describing the MSW collection systems in three Asian countries that are Singapore, Mongolia, and Nepal; by reviewing the literature related to this particular subject. Therefore, by going through the literature, it has been found that the authorities responsible for waste collection are: Public Waste Collectors (PWCs) appointed by National Environment Agency (NEA) in Singapore, the municipal government, and Tohijilt Uilchilgeenii Kompani (TKUs) in Mongolia, and 270 municipalities in Nepal. Along with this, the waste collection fee in Singapore is paid to Singapore Power (combined with utility bills); in Mongolia to TKUs (based on their performance); and in Nepal, it is fixed on ad hoc basis. Overall, based on the practices of waste collection discussed in this article, Singapore has a better waste collection system than that Mongolia and Nepal.